Performance of Immobilized Chlorella Algae for Removing pb(II) Ions from Aqueous Solution - Abdulkareem, Hala N.; Alwared, Abeer I. (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
This study aims to show the effectiveness of immobilization of Chlorella green algae biomass in the form of bead for the removal of lead ions from synthetic polluted water at various operational parameters such as pH (2–6), biosorbent dosage (0.5–20 g/L) and initial concentration (10–100 mg/L). More than 90 % removal efficiency was achieved. FTIR and SEM-EDX analysis of the biosorbent before and after sorption show differences in the functional groups on the adsorbent surface. Langmuir and Freundlich equilibrium isotherm, pseudo-first-order and pseudo-second-order kinetic models were applied to the experimental and results and show good conformity with Langmuir isotherm model and pseudo-second-order kinetic model with correlation coefficient (0.994) and (0.998) respectively.